2020
DOI: 10.3390/biomedicines8120595
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol Induced Cell Cycle Arrest and Apoptosis in Glioblastoma Cells

Abstract: Although several antipsychotic drugs have been shown to possess anticancer activities, haloperidol, a “first-generation” antipsychotic drug, has not been extensively evaluated for potential antineoplastic properties. The aim of this study was to investigate the antitumoral effects of haloperidol in glioblastoma (GBM) U87, U251 and T98 cell lines, and the effects of combined treatment with temozolomide (TMZ) and/or radiotherapy, using 4 Gy of irradiation. The viability and proliferation of the cells were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In addition, Papadopoulos et al . showed that alteration in the expression of CD24 and CD44 genes using haloperidol in GBM U87MG, U251, and T98 cell lines induces M/G2 cell cycle arrest and increases the population of cells in the G0/G1 phase ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Papadopoulos et al . showed that alteration in the expression of CD24 and CD44 genes using haloperidol in GBM U87MG, U251, and T98 cell lines induces M/G2 cell cycle arrest and increases the population of cells in the G0/G1 phase ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, antipsychotic drugs have emerged as potential anticancer agents, whereas 12 candidate substances have been identified [117,118]. Treatment with haloperidol, in particular, has been reported to promote G2/M cell cycle arrest in the U87 GBM cell line [119].…”
Section: Targeting the Cell Cycle Machinery In Gbmmentioning
confidence: 99%
“…However, haloperidol is a non-selective inhibitor for D2 receptors and also has antimuscarinic, anti-adrenergic (a1), and antihistaminic (H1) effects [ 10 , 11 ]. Except for its use as an antipsychotic drug, haloperidol has also been found, mainly at an experimental level, to have anti-neoplastic, anti-fungal, anti-viral, and immunomodulatory properties [ 12 , 13 , 14 , 15 ].…”
Section: Typical Antipsychoticsmentioning
confidence: 99%
“…Regarding its antineoplastic properties, haloperidol has been found to induce autophagy, apoptosis, and cell cycle arrest [ 15 , 16 ]. In an in vitro study, Papadopoulos et al observed that glioblastoma (GBM) U87, U251, and T-98 cell lines are sensitive to haloperidol.…”
Section: Typical Antipsychoticsmentioning
confidence: 99%
See 1 more Smart Citation